Continuous arch and rectangular loops for the correction of consistent and inconsistent load systems in extruded and tipped maxillary second molars - Shintcovsk, Ricardo Lima; Martins, Lidia Parsekian [UNESP]; Shintcovsk, Luegya Knop; Tanaka, Orlando Motohiro; Martins, Renato Parsekian [UNESP] (Elsevier B.V., 2018)
Introduction: The aim of this research was to compare the load systems produced by rectangular loops and continuous arches for the correction of extruded second molars with a mesial inclination (inconsistent system) and a distal inclination (consistent system). Methods: The maxillary first molar of an acrylic model of a patient, with passive brackets and tubes bonded, was connected to a 3-dimensional load cell of an orthodontic force tester, and the second molar was replaced by its respective tube bonded to a second load cell. The second molar tube was moved 2.5 mm occlusally and tipped 20 degrees mesially and distally, creating an inconsistent force system and a consistent force system. For each situation, ten 0.017 x 0.025-in beta-titanium, 8 x 10-mm rectangular loops were compared with 10 0.014-in nickel-titanium continuous arches. The vertical forces-F(z)-and tipping moments-M(x)-were compared using 4 t tests, at 5%. Results: In the inconsistent group, the rectangular loop produced a larger M(x) in both molars: 2.11 N.mm in the second molar compared with the 0.15 N.mm of the continuous arches. On the first molar, the rectangular loops produced -5.58 N.mm against -2.08 N.mm produced by the continuous arches. The F(z) values produced at the second molar with each system were similar, whereas on the first molar they were different; the rectangular loops produced 0.41N, and continuous arches produced 0.53N. In the consistent group, the rectangular loops produced smaller M(x) values at the second molar (-3.06 N.mm) than did the continuous arch (-4.25 N.mm) (P = 0.01), as well as a smaller F(z) value (-0.52 vs -0.92 N, respectively). At the first molar, the rectangular loops produced smaller M(x) values (-2.32 N.mm) than did the continuous arch (-4.18 N.mm), as well as a smaller F(z) value (0.59 vs 1.10 N). Conclusions: In the inconsistent group, only the rectangular loop produced a system of force that could correct the second molar. In the consistent system, both group mechanics produced a system of force compatible with the correction of the second molar, but the continuous wire produced larger moments. Both groups showed a tendency for mesial crown tipping of the first molar.